Machaut's Music: New Interpretations - Leach, Elizabeth Eva (Suffolk Boydell & Brewer, 2003)
Guillaume de Machaut (1300-1377) is regarded as the greatest French poet-composer of the middle ages, as he was during his lifetime. A trained secretary, with a passion for collecting, copying and ordering his own work, the number of surviving notated musical works attributed to him far exceeds that of any of his contemporaries. All the main genres of song - lais, virelais, balades, and rondeaux - together with Machaut's motets, and his famous Mass cycle are considered here from a variety of perspectives. These incorporate the latest scholarly understanding of both Machaut's poetry and music, and the material form they take when notated in the surviving manuscripts. The book thus presents a detailed picture of the current range of interpretative approaches to Machaut's music, focusing variously on counterpoint, musica ficta, text setting, musico-poetic meanings, citation and intertextuality, tonality, and compositional method. Several of Machaut's works are discussed by a pair of contributors, who reach conclusions at times mutually reinforcing or complementary, at times contradictory and mutually exclusive. That Machaut's music thrives on such constructive debate and disagreement is a tribute to his scope as an artist, and his musico-poetic achievement. Contributors: JENNIFER BAIN, MARGARET BENT, CHRISTIAN BERGER, JACQUES BOOGAART, THOMAS BROWN, ALICE V. CLARK, JANE E. FLYNN, JEHOASH HIRSHBERG, KARL KUEGLE, ELIZABETH EVA LEACH, DANIEL LEECH-WILKINSON, ETER M. LEFFERTS, WILLIAM PETER MAHRT, KEVIN N. MOLL, VIRGINIA NEWES, YOLANDA PLUMLEY, OWEN REES, ANNE STONE. ELIZABETH EVA LEACH lectures in music at Royal Holloway, University of London.
Keywords: Machaut, Guillaume de -- c. 1300-1377; Middle Ages (500-1400); Vocal music; Burgundy (France)